Observations from Faculty Development Workshops in the Current Indian Context - Krishnan, Sivakumar (Journal of Engineering Education Transformations, 2018)
More and more higher education administrators in India are recognizing the imperative need for new faculty development. Many ’fresher’ engineering faculty are eager and motivated to teach using innovative teaching methods that are student-centred and experimenting in their classrooms. However very few of them have industry experience and most begin teaching right after their post graduation. Given this scenario, what approaches can they take to create practical and relevant content for their classes? A hierarchical organization structure also constraints many young faculty initiatives. Then, there are curricular constraints resulting from the affiliated or autonomous status of the institutions. How can faculty and management address these constraints as well as student resistance to new approaches? In this context, as part of the IIEECP (IUCEE-IGIP International Engineering Educator Certification Programme), an attempt has been made by several institutional leaders and IUCEE to offer faculty development workshops in 3 phases. The scope of this paper is restricted to the experience of seven Phase 1 3-day workshops involving approximately 300 faculty members from various engineering institutions in India. The workshop sessions were highly interactive including group discussions and activities. The paper will share short summaries of participant survey data and facilitator observations from the workshops. As mentioned in many forums on higher education in India, a concerted and holistic approach involving leadership of forward thinking private higher educational institutions as well as academic and administrative bodies is long due to address issues regarding educational effectiveness at higher education institutions in India.